PARALLEL IMPORT IN UZBEKISTAN AND SOME CENTRAL ASIAN COUNTRIES - Dinara Abdunayimova (Scholar Express Journals, 2021)
In this article, the author explains the concept of «parallel import» highlights its features and explains the difference between grey and counterfeit goods. Moreover, the author shows the experience and legislation of individual countries such as Uzbekistan and Kazakhstan, and the attitude of these countries to parallel import. Furthermore, the reasons why parallel import should or should not be supported by the state are explained in the following examples.
Keywords: Parallel import, grey import, goods, counterfeit, illegal import, legislation